Progress in the electrochemical modification of graphene-based materials and their applications - Chakrabarti,MH; Low,CTJ; Brandon,NP; Yufit,V; Hashim,MA; Irfan,MF; Akhtar,J; Ruiz-Trejo,E; Hussain,MA (Electrochimica Acta, 2013)
Graphene is a 2D allotrope of carbon with exciting properties such as extremely high electronic conductivity and superior mechanical strength. It has considerable potential for applications in fields such as bio-sensors, electrochemical energy storage and electronics. In most cases, graphene has been functionalized and modified with other materials to prepare composites. This work reviews the electrochemical modification of graphene. Commencing with a brief history, a summary of several different means of modifying graphene to effect diverse applications is provided. This is followed by a discussion on different composite materials that have been prepared with reduced graphene oxide prior to moving onto a detailed consideration of six different methods of electrochemically modifying graphene to prepare composite materials. These methods involve cathodic reduction of graphene oxide, electrophoretic deposition, electro-deposition techniques, electrospinning, electrochemical doping and electrochemical polymerization. Finally a consideration on the applications of electrochemically modified graphene composite materials in various fields is presented prior to discussing some prospects in enhancing the electrochemical process to realize excellent and economic composite materials in bulk.